PERAN SANIRI NEGERI DALAM MENYALURKAN ASPIRASI MASYARAKAT TERHADAP PENYUSUNAN PROGRAM PEMBANGUNAN NEGERI TIAL KABUPATEN MALUKU TENGAH - Farah Lessy; Wahab Tuanaya; Marno Wance (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2021)
the research was conducted to figure out the role of Saniri, an institution in a village, in conducting programs of development planning at the village with custom status (Negeri). The limited experience and the lack of education possessed by traditional institution members (Saniri) were the initial reason that led the researchers to conduct this in-depth research. The following reason was that Saniri has a joint planning function with the head of the village called Kepala Raja. This study used a quantitative approach by dividing the samples into 17 government and Saniri institutions and 80 public communities. The result reveals that the calculation of the product-moment correlation shows a positive relationship and influence between the two variables. This result means that the role of Saniri Negeri in channeling community aspirations has a positive role in influencing the preparation of development programs in Negeri Tial, Salahutu District, Central Maluku Regency.